How the growth rate influences low-carbon sustainable production performance under different disposabilities in China's manufacturing industries?. (10th March 2020) - zhang, Wei; Lin, Weiwen; Li, Zhenpeng
Abstract: An improved understanding of the influence of growth rates under different disposabilities on low-carbon sustainable production performance (LCSPP) can aid China's manufacturing industries (MIs) to synchronize productivity enhancement and carbon emission abatement. To demonstrate the relationship between the growth rates under different disposabilities and their LCSPP well, this work provides the following contributions: (a) The effects of growth rate on LCSPP under different development models are analyzed using the disposability framework in economics; (b) the data envelopment analysis (DEA) model for estimating industrial LCSPP is explored by incorporating a non-radial and non-oriented directional distance function (NNDDF) into the DEA environmental assessment; (c) the effects of growth rate on LCSPP under different disposabilities are evaluated by applying econometric models in China's MIs between 2001 and 2015. Results show that growth rates negatively influence the improvement of the LCSPP of China's MIs. The effect on LCSPP is stronger under natural disposability than under managerial disposability. Low-end MIs and heavy chemical industries exert considerable efforts on their economies, while light industries and high-end MIs provide considerable efforts on environmental performance. Some important policy implications are presented on the basis of theoretical analysis and empirical conclusions. Highlights: Growth rate influences the LCSPP improvement of MIs in China's MIs negatively. Developmental model influences LCSPP significantly. Environmental governance contributes to the improvement of LCSPP. R&D density has positive effects on the LCSPP. FDI has negative effect on the LCSPP under natural disposability.